El fortalecimiento del clima escolar como desafío para la enseñanza problematizadora (2019)
The present study was set as a purpose to analyze the strengthening of the school climate from the challenges of problematizing teaching in the second degree of the Sagrada Familia school located in the municipality of Malambo, Atlántico. The type of research is qualitative and the paradigm of this is socio-critical, which allowed generating a social transformation. The emphasis of this research also allowed us to implement different activities in the classroom in order to improve the problems encountered, as well as to demonstrate the pertinence of the problematizing teaching strategy. From the theoretical affirmation supported by Álvarez (2012) who expresses that this "must start from a communication between subjects, that is to say an encounter, there must be a dialogicity that allows a reflection and a process of criticality within the communication to take place" ( P.3). The result was that this strategy implemented reduced conflicts within the classroom and students improved their perception of school climate.